Decreased antibiotic exposure using a procalcitonin protocol for respiratory infections and sepsis in US community hospitals (ProCommunity). (4th May 2021) - DeSear, Kathryn E.; Thompson-Leduc, Philippe; Van Schooneveld, Trevor C.; Kirson, Noam; Chritton, Jacqueline J.; Ie, Sue; Cheung, Hoi Ching; Ou, Susan; Zimmer, Louise; Schuetz, Philipp
Abstract: Objective: Antibiotic overuse leading to antimicrobial resistance is a global public health concern. Clinical trials have demonstrated that procalcitonin-based decision-making for antibiotic therapy can safely decrease inappropriate antibiotic use in patients with respiratory infections and sepsis, but real-world data are scarce. This study sought to assess the impact of a procalcitonin-based antibiotic stewardship program (protocol plus education) on antibiotic use in community hospitals. Methods: An observational, retrospective, matched cohort study was conducted. Eligible patients treated in hospitals with a procalcitonin-based protocol plus education (Procalcitonin cohort hospitals) were matched to patients admitted to facilities without procalcitonin testing (Control cohort hospitals) using a 1:2 ratio. The Control hospitals were facilities where procalcitonin testing was not available on site. Patient matching was based on: (1) age, (2) gender, (3) admission diagnosis code using groupings of the International Classification of Diseases, 10th Revision, (4) whether patients were admitted to the intensive care unit, and (5) whether a blood culture test was performed. Procalcitonin cohort hospitals implemented a quality improvement initiative, where procalcitonin was available, used regularly, and clinicians (physicians and pharmacists) were educated on its use. Results: After adjustment, patients in the Procalcitonin cohort had 1.47 fewer antibiotic days (9.1 vs. 8.5 days, 95%CI: −2.72; −0.22, p  = .021). There was no difference in length of stay or adverse clinical outcomes except for increase in acute kidney injury (odds ratio = 1.26, 95%CI: 1.01; 1.58, p  = .038). Conclusions: Patients with respiratory infections and sepsis in hospitals utilizing a procalcitonin-based protocol coupled with education received fewer days of antibiotic therapy.